HUBUNGAN TINGKAT KEKUATAN OTOT DENGAN PRESTASI ATLET CABANG OLAHRAGA JUDO PADA PEKAN OLAHRAGA NASIONAL (PON) XVIII 2012 DI RIAU - Vita Murniati Tarawan Lubis; Rizky Aji Pambudi; vitriana Biben (PAIFORI, 2018)
Judo is described as a physical contact sport. A judo athlete should try to make themovement of throwing, slamming and holding the opponent's strength during the game. To perform the technique well, muscle strength is important in judo athletes. As one of the components of physical fitness in athletes, muscle strength has an important role for the judo athlete to maximize their performance and have their best achievement. Therefore, this study aims to determine the relationship of muscle strength level of judo athletes with their achievement in Pekan Olahraga Nasional (PON) XVIII 2012 in Riau. A cross-sectional study using the analytical method was done on 19 Judo athletes as subjects. Data are collected from secondary data as a result of muscle strength examination measured by push, pull, and leg dynamometer, conducted by Komite Olah Raga Nasional (KONI) West Java. Judo athletes who participated Pekan Olah Raga Nasional (PON) XVIII 2012 championship in Riau were included while athletes who injured were excluded. In this study judo athletes who won medals (got achievement) were 7 athletes, while those who did not win medals (did not get the achievement) were 12 athletes. The significance value (p-value) for the relationship of muscle strength with judo athlete’s achievement as measured by push dynamometer was 0.764, pull dynamometer was 0.570, and leg dynamometer was 0.132. In conclusion, there isno significant relationship between the level of muscle strength with the judo athlete’s achievement on Pekan Olah Raga Nasional (PON) XVIII 2012.